Health-related quality of life by IBDQ-32 in colombian patients with inflammatory bowel disease in remission: A cross-sectional study - Parra Izquierdo, Viviana (2023)
In Colombia there are no data about perception of quality of life (QoL) in inflammatory bowel disease (IBD). The aim of this study was to determine the perception of QoL by means of the IBDQ-32 questionnaire in patients with IBD from a sample of patients from different referral centers. We carried out a cross-sectional study in adults with IBD in clinical remission, in outpatient follow-up, in 3 institutions in different cities, between June 2022 and November 2022, eligible subjects were identified, information was collected on different dates, about socio-demographic and clinical aspects, and the IBDQ-32 questionnaire was evaluated on one occasion. Descriptive and analytical analysis of the variables evaluated was performed. 80 patients, 70% women, mean age 38.5(range 18-72; SD 13.25) years. 67.5% ulcerative colitis (UC), 32.5% Crohn's disease (CD). Moderate QoL involvement (median 150 points, interquartile range118.3-181.5) was found in IBD, in UC median 151 (interquartile range120-174.75) points, while in CD 133 (interquartile range106.25-186.25) points. There was greater involvement in the systemic domain, with median 21 (interquartile range 15.8-27) points, and 18.5 (interquartile range 12.8-25.3) points, for UC and CD, respectively. The least affected corresponded to the digestive domain and social function, in median UC 48.5 (interquartile range 40-58.3), and 27(interquartile range 20.8-33); in median CD 43 (interquartile range 35.5-61.75) and 24.5(interquartile range 18-32.5), respectively. No statistically significant differences were found. This study provides unique information about QoL with IBD in Colombia. It is necessary to continue reinforcing the accompaniment, support, and education of patients with IBD.